Study on Factors Associated with Poor Seizure Control in Epileptic Patients during Pregnancy (East West Medical College Journal, 2024)
The management of epilepsy during pregnancy is always challenging. This study aims to analyze the factors associated with poor seizure control during pregnancy and to describe the most commonly used antiseizure drugs in these patients. We conducted a casecontrol study of pregnant patients with epilepsy between 2017 and 2022. 50 pregnant women with poorly controlled epilepsy were taken as cases and 50 pregnant women with well-controlled epilepsy were taken as controls. Patients were evaluated in the first and second trimesters of pregnancy and after delivery. Patients’ mean age was 32.6 years. 53% had focal epilepsy, 40% had generalized epilepsy and 5 % had undetermined epilepsy. The factors associated with poor control of seizure during pregnancy were duration of epilepsy, poor seizure control in the year prior to pregnancy, treatment with 2 or more antiseizure drugs, untreated epilepsy, missed medication dosages, decline in plasma concentrations of antiepileptic drug, presence of focal activity in EEG and abnormal imaging findings. Anti-seizure medications most widely used in monotherapy were lamotrigine, levetiracetam, carbamazepine, and valproate.EWMCJ Vol. 12, No. 1&2, January-July 2024: 99-103